The role of actors in the innovation diffusion process of Celugam products - Hediyati Anisia Sinamo; Tasya Ismaya Putri (Sustainable Urban Development and Environmental Impact Journal, 2025)
Background:  This study explores the roles of various actors in the innovation diffusion process of Celugam, a traditional textile product in Liwa City, West Lampung Regency. Celugam holds high cultural value and local economic potential, yet its innovation dissemination faces challenges such as limited artisan regeneration, restricted market access, and insufficient policy attention. Method: Using a descriptive qualitative approach and Rogers’ diffusion of innovation theory, the study analyzes five key stages: knowledge, persuasion, decision, implementation, and confirmation. Data were collected through in-depth interviews, field observations, and content analysis. Findings reveal that the diffusion process is gradual and involves three main actors: artisans as innovators, government as facilitators, and the community as end users. Finding: Artisans contribute through production technique transformation and product diversification, while the government provides training, equipment, and promotional access. The community’s adoption is shaped by cultural values and social validation. The main challenges include low youth interest and suboptimal marketing strategies. The study recommends stakeholder synergy, digital-based promotion, and artisan regeneration programs to ensure Celugam’s sustainability as a culturally rooted creative economic product. These findings serve as a foundation for inclusive and sustainable local economic development policies. Conclusion: This study concludes that the diffusion of Celugam innovation in Liwa City reflects a dynamic interaction between cultural preservation and creative economic adaptation. Novelty/Originality of this article: The novelty of this study lies in its application of Rogers’ Diffusion of Innovation Theory to a traditional textile context, offering an interdisciplinary perspective that bridges cultural heritage studies and innovation diffusion frameworks.